2022
DOI: 10.1177/10556656221074214
|View full text |Cite
|
Sign up to set email alerts
|

Parental Satisfaction from Telemedicine in the Follow-up of Children Operated for Craniosynostosis during COVID-19 Pandemic

Abstract: Objective The current study aimed to evaluate the satisfaction level of parents from telemedicine use in the long-term follow-up of children operated for craniosynostosis during the COVID-19 pandemic. Design A cross-sectional 9-question survey analysis using Qualtrics survey software. Setting An institutional study carried out at a national, tertiary level academic center in the Slovak Republic. Patients All patients operated for non-syndromic and syndromic craniosynostosis in our department, who participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…The authors reported that 72.3% of parents were satisfied with the telemedicine program, and 67.2% found it convenient. However, only 18.7% of them would prefer telemedicine consultations in the future ( 56 ). As a result, it is critical to train clinicians in teledentistry and improve technical limitations to provide better tele-dental care in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that 72.3% of parents were satisfied with the telemedicine program, and 67.2% found it convenient. However, only 18.7% of them would prefer telemedicine consultations in the future ( 56 ). As a result, it is critical to train clinicians in teledentistry and improve technical limitations to provide better tele-dental care in the future.…”
Section: Discussionmentioning
confidence: 99%
“…48 This sharp adoption of telemedicine may be a consideration for families with limited access to cleft and craniofacial centers, 16,49 with peri-COVID-19 data suggest relatively high (over 70%) family satisfaction with telemedicine programs. 49 However, less than 20% of families would prefer telemedicine encounters in the future, suggesting telemedicine may serve as an ad hoc mode of clinical care. 49 Content and accessibility of cleft and craniofacial team information are essential for families to make informed decisions.…”
Section: Social Considerationsmentioning
confidence: 99%
“…49 However, less than 20% of families would prefer telemedicine encounters in the future, suggesting telemedicine may serve as an ad hoc mode of clinical care. 49 Content and accessibility of cleft and craniofacial team information are essential for families to make informed decisions. Recent studies suggest a high proportion (38%) of ACPA-approved cleft and craniofacial team websites are inaccessible, 50 and of those that are, the average reading level was appraised at 10.7, which exceeds the American Medical Association recommendation of a sixth to seventh-grade reading level.…”
Section: Social Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, mental and physical health recovery due to the pressures children face during the implementation of social distancing and school closures. The third is rebuilding children's relationships with the social environment, hampered by the pandemic for two years [1][2][3][4][5][6][7][8]. Based on the studies' tendency about existing children, there have not been studies that view children as individuals who experience a crisis in self-esteem formation as an essential aspect of psychosocial development that determines their well-being.…”
Section: Introductionmentioning
confidence: 99%